O < 3 >-O < 2 > composite phase ternary positive electrode material and preparation method and application thereof

By preparing O3@O2 composite phase ternary cathode material, using multi-step sintering and ion exchange reaction, the problem of limited improvement in cutoff voltage and rate performance of existing cathode materials is solved, and a battery material with high energy density and rate performance is achieved.

CN119560534APending Publication Date: 2025-03-04GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411742606.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The cutoff voltage and rate performance improvement of existing cathode materials is limited, making it difficult to meet the needs of high energy density and rate performance.

Method used

The preparation method of O3@O2 composite phase ternary cathode material is adopted, and the O3@O2 composite phase material is formed through multi-step sintering and ion exchange reaction, thereby improving the structural stability of the material and the lithium ion migration speed.

Benefits of technology

The specific capacity, Coulomb efficiency, cycle performance and rate performance of the material are significantly improved, and good battery performance can be maintained under high voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560534A_ABST
    Figure CN119560534A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of positive electrode materials, and particularly relates to an O < 3 >-O < 2 > composite phase ternary positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: S1, mixing a ternary positive electrode material precursor, a first lithium source and a dopant, and carrying out first sintering to obtain a matrix; s2, mixing the matrix, a sodium source and a cobalt source, and carrying out second sintering to obtain an O3 (at) P2 composite phase material; s3, mixing the O3-coated P2 composite phase material and a second lithium source, and carrying out ion exchange reaction; and S4, mixing the ion exchange product and a coating agent, and carrying out third sintering to obtain the O3 and O2 composite phase ternary positive electrode material, according to the invention, doping, phase transformation and coating have a synergistic effect, and a battery containing the ternary positive electrode material prepared by the invention has excellent specific capacity, coulombic efficiency, cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and specifically relates to an O3@O2 composite phase ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the lithium-ion battery industry, high-energy-density lithium-ion batteries are becoming more and more popular. How to improve the energy density of single-crystal ternary materials is an urgent problem to be solved in battery technology.

[0003] Some scholars have increased the energy density of materials by doping certain elements to increase the battery's charge cut-off voltage. Although the above technical means effectively increase the energy density of materials, the material's cycle performance will be affected to a certain extent. At present, the 4.45V cut-off voltage is already the highest voltage of single-crystal ternary materials. To further increase the battery's charge cut-off voltage, doping alone is far from enough; some scholars have also used phase transformation methods to increase the cut-off voltage of single-crystal ternary positive electrode materials; but these methods have limited effects on the cut-off voltage.

[0004] At the same time, how to improve the rate performance is also one of the focuses of positive electrode material research. However, the existing methods of changing the battery core structure and treating the surface of the positive electrode material to improve the rate performance are relatively cumbersome and have limited improvement in rate performance. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the limited improvement of the cut-off voltage and rate performance of existing positive electrode materials, thereby providing an O3@O2 composite phase ternary positive electrode material and its preparation method and application.

[0006] To this end, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing an O3@O2 composite phase ternary positive electrode material, wherein the preparation method comprises the following steps:

[0008] S1, mixing a ternary cathode material precursor, a first lithium source, and a dopant, and performing a first sintering to obtain a matrix;

[0009] S2, mixing the matrix, the sodium source and the cobalt source, and performing a second sintering to obtain an O3@P2 composite phase material;

[0010] S3, mixing the O3@P2 composite phase material and the second lithium source to perform an ion exchange reaction;

[0011] S4, mixing the ion exchange product and the coating agent, and performing a third sintering to obtain an O3@O2 composite phase ternary positive electrode material.

[0012] In the present invention, XRD test is performed to prove the existence of O3@P2 composite phase.

[0013] According to the present invention, the first sintering conditions include: the first sintering temperature is 900-1000°C, and the time is 8-12h; the second sintering conditions include: the second sintering temperature is 600-750°C, and the time is 6-10h; the third sintering conditions include: the third sintering temperature is 300-500°C, and the time is 4-8h.

[0014] According to the present invention, the molar ratio of the sum of the metal elements in the precursor to the sum of the metal elements in the coating agent is 1:0.002-0.007.

[0015] According to the present invention, the coating agent includes at least one of an aluminum source and a tungsten source.

[0016] According to the present invention, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide or aluminum inorganic salt; further optionally, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate.

[0017] According to the present invention, the tungsten source includes at least one of tungsten oxide, tungsten acid or tungstate; further optionally, the tungsten source includes at least one of tungsten oxide, tungstic acid and ammonium paratungstate.

[0018] According to the present invention, when the coating agent is an aluminum source and a tungsten source, the molar ratio of the aluminum element in the aluminum source to the tungsten element in the tungsten source is (2-6):(1-6).

[0019] According to the present invention, in S1, the molar ratio of the lithium element in the first lithium source, the metal element in the precursor, and the metal element in the dopant is (1.02-1.05):1:(0.001-0.006).

[0020] According to the present invention, in S1, the dopant comprises a metal oxide.

[0021] According to the present invention, the metal oxide includes at least one of aluminum oxide, zirconium oxide and yttrium oxide.

[0022] According to the present invention, when the doping agents are aluminum oxide and zirconium oxide, the molar ratio of the aluminum element of the aluminum oxide to the zirconium element of the zirconium oxide is 1:(1-2).

[0023] According to the present invention, in S2, the molar ratio of the sum of metal ions in the precursor, the sodium element in the sodium source, and the cobalt element in the cobalt source is 1:(0.005-0.010):(0.006-0.012).

[0024] According to the present invention, the sodium source comprises sodium salt and / or sodium-containing alkali; further optionally, the sodium source comprises at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.

[0025] According to the present invention, the cobalt source includes at least one of cobalt-containing oxides, cobalt oxyhydroxides, and cobalt-containing hydroxides; further optionally, the cobalt source includes at least one of cobalt oxide, cobalt oxyhydroxide, and cobaltous hydroxide.

[0026] According to the present invention, the molar ratio of the lithium element in the second lithium source to the sodium element in the sodium source is 1-10:1.

[0027] According to the present invention, the conditions of the ion exchange reaction include: the temperature of the ion exchange reaction is 200-400° C., and the time is 1-8 hours.

[0028] The second aspect of the present invention protects an O3@O2 composite phase ternary positive electrode material prepared by the aforementioned preparation method.

[0029] A third aspect of the present invention protects a secondary battery, wherein the secondary battery comprises the aforementioned O3@O2 composite phase ternary positive electrode material.

[0030] The battery preparation method comprises the following steps: mixing the prepared positive electrode material, polyvinylidene fluoride (PVDF), and acetylene black with N-methylpyrrolidone (NMP) in a mass ratio of 96:(2-2.5):(2-2.5), wherein the mass ratio of solid to liquid is 7:2.5-3.5, to prepare a positive electrode slurry; and uniformly mixing the negative electrode material graphite, the binder LA133, and the carbon nanotubes CNT in a mass ratio of 92:(5-6):(2-2.5) to prepare a mixed negative electrode slurry; and then preparing a finished soft-pack battery by coating-rolling-slicing-winding-assembly-liquid injection-formation-secondary sealing-capacity division and the like.

[0031] The technical solution of the present invention has the following advantages:

[0032] 1. The present invention provides a method for preparing an O3@O2 composite phase ternary positive electrode material, wherein the preparation method comprises the following steps: S1, mixing a ternary positive electrode material precursor, a first lithium source, and a dopant, and performing a first sintering to obtain a matrix; S2, mixing the matrix, a sodium source, and a cobalt source, and performing a second sintering to obtain an O3@P2 composite phase material; S3, mixing the O3@P2 composite phase material and a second lithium source, and performing an ion exchange reaction; S4, mixing the ion exchange product and a coating agent, and performing a third sintering to obtain an O3@O2 composite phase ternary positive electrode material; wherein the matrix is ​​an O3 phase, after adding a sodium source and a cobalt source, the sodium source and the cobalt source will exist as coating materials on the interface of the O3 phase, and then a P2 phase coating material is formed on the interface of the O3 phase material, and an ion exchange reaction is performed, and lithium ions and sodium ions are ion exchanged. , and the O3@O2 coexistence phase is obtained. Because sodium ions have a larger radius, the embedding and extraction processes are more complicated. After ion exchange, the new radius of the material level that adapts to lithium ions changes accordingly, avoiding the disadvantages brought by sodium ions. During use, after high voltage is applied to dissolve lithium ions, the O3@O2 composite phase ternary positive electrode material is in a delithiation state. The synergistic effect of bulk multi-element doping, composite phase integration and multi-element coating improves the stability of the material structure and interface, reduces the possibility of collapse of the bulk structure of the material and the risk of particle rupture, and accelerates the speed of lithium ion movement and migration. In addition, the existence of the O2 phase layer can further improve the stability of the battery positive electrode material interface, reduce the interface impedance, and increase the transmission rate of lithium ions, so that the O3@O2 composite phase ternary positive electrode material exhibits excellent specific capacity, coulombic efficiency, cycle performance and rate performance.

[0033] 2. The specific molar ratio of the sum of metal elements in the ternary positive electrode material precursor and the sum of metal elements in the coating agent, the specific type of the coating agent, the specific molar ratio of the sum of metal ions in the ternary positive electrode material precursor, the sodium element in the sodium source, and the cobalt element in the cobalt source in the present invention can further improve the specific capacity, coulombic efficiency, cycle performance and rate performance of the positive electrode material.

[0034] 3. When the dopant is aluminum oxide, the cycle performance of the positive electrode material can be further improved. When the dopant is zirconium oxide, the capacity of the positive electrode material can be further improved.

[0035] 4. The specific conditions of ion exchange in the present invention can further optimize the reaction effect, thereby further improving the electrical properties of the prepared positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 XRD image of the O3@O2 composite phase ternary cathode material of Example 1. DETAILED DESCRIPTION

[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0040] Example 1

[0041] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0042] S1, mixing a ternary positive electrode material precursor, lithium carbonate, aluminum oxide, and zirconium oxide, and performing a first sintering to obtain a matrix; the molar ratio of lithium element in lithium carbonate, the sum of metal elements of nickel element, cobalt element, and manganese element in the ternary positive electrode material precursor, aluminum element in aluminum oxide, and zirconium element in zirconium oxide is 1.04:1:0.0015:0.002; sintering is performed in an oxygen atmosphere, the sintering temperature is 950° C., and the time is 10 hours;

[0043] S2, mixing the matrix, cobaltous hydroxide and sodium carbonate, and performing a second sintering to obtain an O3@P2 composite phase material; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate, and the cobalt element in cobaltous hydroxide is 1:0.007:0.010; calcination is carried out in an oxygen atmosphere, the sintering temperature is 750°C, and the time is 8 hours;

[0044] S3, mixing the O3@P2 composite material and lithium hydroxide, performing an ion exchange reaction, and obtaining an ion exchange product; wherein the molar ratio of the lithium element in the lithium hydroxide to the sodium element in the sodium carbonate is 3:1; the temperature of the ion exchange reaction is 280° C., and the time is 3 hours;

[0045] S4, mixing the ion exchange product, aluminum oxide and tungsten oxide, coating and sintering to obtain O3@O2 composite phase ternary positive electrode material; wherein the molar ratio of the sum of metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of metal elements in the coating agent is 1:0.003, the molar ratio of aluminum element to tungsten element in the coating agent is 2:1, and the coating and sintering are carried out in an oxygen atmosphere at a temperature of 400°C for 6 hours to obtain O3@O2 composite phase ternary positive electrode material. The XRD image of the O3@O2 composite phase ternary positive electrode material is as shown in Figure 1 As shown, Figure 1 It can be seen that O2 phase and O3 phase exist. The position of the diffraction peak of O2 phase completely corresponds to the standard card PDF#54-0894, and the position of the diffraction peak of O3 completely corresponds to the standard card PDF#85-1979. The peak heights of I003 (near 19°) and I104 (near 44°) are very different, indicating that the layered structure is more obvious and the degree of lithium-nickel mixing is very low, which is conducive to the release and embedding of lithium ions.

[0046] Example 2

[0047] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0048] S1, mixing a ternary positive electrode material precursor, lithium carbonate, aluminum oxide, and zirconium oxide, and performing a first sintering to obtain a matrix; the molar ratio of lithium element in lithium carbonate, the sum of metal elements of nickel element, cobalt element, and manganese element in the ternary positive electrode material precursor, aluminum element in aluminum oxide, and zirconium element in zirconium oxide is 1.045:1:0.001:0.0015; sintering is performed in an oxygen atmosphere, the sintering temperature is 960° C., and the time is 10 hours;

[0049] S2, mixing the matrix, cobaltous hydroxide and sodium carbonate, and performing a second sintering to obtain an O3@P2 composite phase material; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate, and the cobalt element in cobaltous hydroxide is 1:0.010:0.0065; calcination is carried out in an oxygen atmosphere, the sintering temperature is 700°C, and the time is 7h;

[0050] S3, mixing the O3@P2 composite material and lithium hydroxide, performing an ion exchange reaction, and obtaining an ion exchange product; wherein the molar ratio of the lithium element in the lithium hydroxide to the sodium element in the sodium carbonate is 4:1; the temperature of the ion exchange reaction is 300° C., and the time is 3 hours;

[0051] S4, mixing the ion exchange product, aluminum oxide and tungsten oxide, coating and sintering to obtain an O3@O2 composite phase ternary positive electrode material; wherein the molar ratio of the sum of metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of metal elements in the coating agent is 1:0.004, the molar ratio of aluminum and tungsten in the coating agent is 3:1, and the sintering after coating is carried out in an oxygen atmosphere at a temperature of 450°C for 6 hours.

[0052] Example 3

[0053] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0054] The method of Example 1 is the same, except that in S4, the ion exchange product, aluminum oxide and tungsten oxide are mixed, coated and sintered to obtain an O3@O2 composite phase ternary positive electrode material; wherein the molar ratio of the sum of metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of metal elements in the coating agent is 1:0.006, and the molar ratio of aluminum and tungsten in the coating agent is 3:1.

[0055] Example 4

[0056] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0057] The method of Example 1 is the same, except that in S4, the coating agent is aluminum oxide.

[0058] Example 5

[0059] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0060] The method of Example 1 is different in that, in S2, the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the cobalt element in cobaltous hydroxide and the sodium element in sodium carbonate is 1:0.006:0.011.

[0061] Example 6

[0062] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0063] The method of Example 1 is the same, except that in S1, the dopant is aluminum oxide.

[0064] Example 7

[0065] This embodiment provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is specifically as follows:

[0066] The method of Example 1 is the same, except that the molar ratio of the aluminum element in the aluminum oxide to the zirconium element in the zirconium oxide is 0.002:0.002.

[0067] Comparative Example 1

[0068] This comparative example provides a method for preparing a ternary positive electrode material, which is as follows:

[0069] The ternary positive electrode material precursor, lithium carbonate, aluminum oxide and zirconium oxide are mixed and subjected to the first sintering to obtain a matrix; the molar ratio of the lithium element in the lithium carbonate, the sum of the metal elements of the nickel element, the cobalt element and the manganese element in the ternary positive electrode material precursor, the aluminum element in the aluminum oxide and the zirconium element in the zirconium oxide is 1.04:1:0.0015:0.002; the sintering is carried out in an oxygen atmosphere at a sintering temperature of 950°C for 10 hours to obtain a ternary positive electrode material.

[0070] Comparative Example 2

[0071] This comparative example provides a method for preparing a ternary positive electrode material, which is as follows:

[0072] S1, mixing a ternary positive electrode material precursor, lithium carbonate, aluminum oxide, and zirconium oxide, and performing a first sintering to obtain a matrix; the molar ratio of lithium element in lithium carbonate, the sum of metal elements of nickel element, cobalt element, and manganese element in the ternary positive electrode material precursor, aluminum element in aluminum oxide, and zirconium element in zirconium oxide is 1.04:1:0.0015:0.002; sintering is performed in an oxygen atmosphere, the sintering temperature is 950° C., and the time is 10 hours;

[0073] S2, mixing the substrate, aluminum oxide and tungsten oxide, coating and sintering to obtain a ternary positive electrode material; wherein the molar ratio of the sum of metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of metal elements in the coating agent is 1:0.003, the molar ratio of aluminum and tungsten in the coating agent is 2:1, and the sintering after coating is carried out in an oxygen atmosphere at a temperature of 400°C for 6 hours.

[0074] Comparative Example 3

[0075] This comparative example provides a method for preparing a ternary positive electrode material, which is as follows:

[0076] S1, mixing a ternary positive electrode material precursor, lithium carbonate, aluminum oxide, and zirconium oxide, and performing a first sintering to obtain a matrix; the molar ratio of lithium element in lithium carbonate, the sum of metal elements of nickel element, cobalt element, and manganese element in the ternary positive electrode material precursor, aluminum element in aluminum oxide, and zirconium element in zirconium oxide is 1.04:1:0.0015:0.002; sintering is performed in an oxygen atmosphere, the sintering temperature is 950° C., and the time is 10 hours;

[0077] S2, mixing the matrix, cobaltous hydroxide and sodium carbonate, and performing a second sintering to obtain an O3@P2 composite phase material; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate, and the cobalt element in cobaltous hydroxide is 1:0.010:0.007; calcination is carried out in an oxygen atmosphere, the sintering temperature is 750°C, and the time is 8 hours;

[0078] S3, mixing the O3@P2 composite material, aluminum oxide and tungsten oxide, coating and sintering to obtain a ternary positive electrode material; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of the metal elements in the coating agent is 1:0.003, the molar ratio of the aluminum element to the tungsten element in the coating agent is 2:1, the sintering after coating is carried out in an oxygen atmosphere, the sintering temperature after coating is 400°C, and the time is 6 hours.

[0079] Comparative Example 4

[0080] This comparative example provides a method for preparing an O3@O2 composite phase ternary positive electrode material, which is as follows:

[0081] The method of Example 1 is different in that in S1, the ternary positive electrode material precursor and lithium carbonate are mixed and the first sintering is performed to obtain a matrix; the molar ratio of the total metal elements of lithium element in lithium carbonate and nickel element, cobalt element and manganese element in the ternary positive electrode material precursor is 1.04:1; the sintering is carried out in an oxygen atmosphere, the sintering temperature is 950°C, and the time is 10 hours.

[0082] Comparative Example 5

[0083] This comparative example provides a method for preparing a composite phase ternary positive electrode material, which is as follows:

[0084] The method of Example 1 is the same, except that step S4 is omitted, and the obtained ion exchange product is an O3@O2 composite phase ternary positive electrode material.

[0085] Test Case

[0086] At 25° C., the battery preparation method is as follows: the positive electrode material, polyvinylidene fluoride (PVDF), and acetylene black prepared in the embodiment and the comparative example are mixed with N-methylpyrrolidone (NMP) in a mass ratio of 96:2:2, wherein the mass ratio of solid to liquid is 7:3, to prepare a positive electrode slurry; the negative electrode material graphite, the binder LA133 and the carbon nanotube CNT are evenly mixed in a mass ratio of 92:6:2 to prepare a mixed negative electrode slurry; and the positive and negative electrode slurries are then subjected to the processes of coating-rolling-slicing-winding-assembly-liquid injection-formation-secondary sealing-capacity division to prepare a finished soft-pack battery.

[0087] The battery was charged to 4.5V at a rate of 0.1C to obtain the first charge specific capacity; then discharged to 3V at a rate of 0.1C to obtain the first discharge specific capacity; the first coulomb efficiency was the first charge specific capacity / first discharge specific capacity × 100%;

[0088] At 45°C, the battery is charged to 4.5V at a rate of 0.5C, and then discharged to 3V at a rate of 0.5C for 500 cycles. The capacity retention rate of the Xth week = the discharge specific capacity of the Xth week / the discharge specific capacity of the first week) × 100%, where X = 100, 200, 300, 400 or 500;

[0089] At 25°C, charge the battery to 4.5V at a rate of 0.2C, and then discharge it to 3V at a rate of 0.2C, and record the discharge specific capacity; charge it to 4.5V at a rate of 0.5C, and then discharge it to 3V at a rate of 0.5C, and record the discharge specific capacity; charge it to 4.5V at a rate of 1C, and then discharge it to 3V at a rate of 1C, and record the discharge specific capacity; charge it to 4.5V at a rate of 3C, and then discharge it to 3V at a rate of 3C, and record the discharge specific capacity, nC rate performance = nC discharge specific capacity / first cycle 0.1C discharge specific capacity × 100%.

[0090] The specific test results are shown in Table 1 and Table 2.

[0091] Table 1

[0092]

[0093] Table 2

[0094]

[0095]

[0096] By comparing the embodiments of the present invention with the comparative examples, it can be seen that there is a synergistic effect among doping, phase transformation and coating during the preparation process, and the battery of the prepared ternary positive electrode material has excellent specific capacity, coulombic efficiency, cycle performance and rate performance.

[0097] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing an O3@O2 composite phase ternary cathode material, characterized in that: The preparation method comprises the following steps: S1, mixing a ternary cathode material precursor, a first lithium source, and a dopant, and performing a first sintering to obtain a matrix; S2, mixing the matrix, the sodium source and the cobalt source, and performing a second sintering to obtain an O3@P2 composite phase material; S3, mixing the O3@P2 composite phase material and the second lithium source to perform an ion exchange reaction; S4, mixing the ion exchange product and the coating agent, and performing a third sintering to obtain an O3@O2 composite phase ternary positive electrode material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the total amount of metal elements in the precursor to the total amount of metal elements in the coating agent is 1:0.002-0.

007.

3. The preparation method according to claim 1, characterized in that: The coating agent includes at least one of an aluminum source and a tungsten source.

4. The preparation method according to claim 3, characterized in that: The aluminum source includes at least one of aluminum oxide, aluminum hydroxide or aluminum inorganic salt; further optionally, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate; Optionally, the tungsten source includes at least one of tungsten oxide, tungstic acid or tungstate; further optionally, the tungsten source includes at least one of tungsten oxide, tungstic acid and ammonium paratungstate; Optionally, when the coating agent is an aluminum source and a tungsten source, the molar ratio of the aluminum element in the aluminum source to the tungsten element in the tungsten source is (2-6):(1-6).

5. The preparation method according to any one of claims 1 to 4, characterized in that: In S1, the molar ratio of the lithium element in the first lithium source, the metal element in the precursor, and the metal element in the dopant is (1.02-1.05):1:(0.001-0.006).

6. The preparation method according to any one of claims 1 to 5, characterized in that: In S1, the dopant includes a metal oxide; Optionally, the metal oxide includes at least one of aluminum oxide, zirconium oxide, and yttrium oxide; Optionally, when the dopants are aluminum oxide and zirconium oxide, the molar ratio of the aluminum element of the aluminum oxide to the zirconium element of the zirconium oxide is 1:(1-2).

7. The preparation method according to any one of claims 1 to 6, characterized in that: The molar ratio of the sum of the metal ions in the precursor, the sodium element in the sodium source, and the cobalt element in the cobalt source is 1:(0.005-0.010):(0.006-0.012); Optionally, the sodium source comprises sodium salt and / or sodium-containing alkali; further optionally, the sodium source comprises at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide; Optionally, the cobalt source includes at least one of cobalt-containing oxides, cobalt oxyhydroxides, and cobalt-containing hydroxides; further optionally, the cobalt source includes at least one of cobalt oxide, cobalt oxyhydroxide, and cobaltous hydroxide.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The molar ratio of the lithium element in the second lithium source to the sodium element in the sodium source is 1-10:1; And / or, the first sintering conditions include: the first sintering temperature is 900-1000° C., and the time is 8-12 hours; And / or, the second sintering conditions include: the second sintering temperature is 600-750° C., and the time is 6-10 h; And / or, the conditions of the third sintering include: the temperature of the third sintering is 300-500° C., and the time is 4-8 hours; And / or, the conditions of the ion exchange reaction include: the temperature of the ion exchange reaction is 200-400° C., and the time is 1-8 hours.

9. An O3@O2 composite phase ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the O3@O2 composite phase ternary positive electrode material as claimed in claim 9.

Citation Information

Cited By

  • Double-coated ternary positive electrode material as well as preparation method and application thereof

    CN120573764A